Upper and Lower Bounds of a Solution of the Cauchy Problem for a Stochastic Differential Equation of Parabolic Type with Power Nonlinearities (Weak Source) - Mel'nik, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We study the time evolution of a solution of the Cauchy problem for a stochastic differential equation of the parabolic type with power nonlinearities. We construct upper and lower bounds for this solution.